COMPARATIVE ANALYSIS OF THE PERFORMANCE OF 3G NETWORKS VOICE SERVICE IN IBADAN METROPOLIS - HAMMED OYEBAMIJI LASISI; IDOWU OLAMIDE HUSSEIN; MUHAMMED BABAJUDE HAMMED; OLAJIDE MICHEAL ODOFIN (Journal of Engineering Studies and Research)
This paper aims to offer a comparative analysis of the main Nigerian mobile network service provider with reference to 3G voice service. Drive tests were engaged in Ibadan metropolis to acquire some KPI parameters used for the analysis. The findings show that not a single service provider was in good standing across all the KPIs. Thus, the performance of a particular operator is purely a function of the desired KPI parameter.